2007
DOI: 10.1080/10903120601023396
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Disaster Medical Assistance Team (DMAT) Deployments in the United States

Abstract: The majority (over 80%) of DMAT team deployments from 1985 through 2002 were for natural disasters, although there has been an increase in "man-made" disasters in recent years with terrorist attacks being the most frequent man-made disaster. DMAT teams have also been deployed on missions outside the United States, most often responding to earthquakes and secondly for hurricanes/tropical storms. There has been a prevalence of "water-related" natural disasters including hurricanes/tropical storms and floods, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…In recent years, DMATs have been called on to respond to a growing number of water-related disasters, consistent with the climate change trend of more frequent severe precipitation events. 126 The NDMS's role was apparent in the response to Hurricane Katrina, as was the role of EM in general, as noted above.…”
Section: Effects On Em's Prehospital Mission: Ems and Disaster Responsementioning
confidence: 87%
“…In recent years, DMATs have been called on to respond to a growing number of water-related disasters, consistent with the climate change trend of more frequent severe precipitation events. 126 The NDMS's role was apparent in the response to Hurricane Katrina, as was the role of EM in general, as noted above.…”
Section: Effects On Em's Prehospital Mission: Ems and Disaster Responsementioning
confidence: 87%
“…According to Briere and Elliott (2000), in the United States the most prevalent natural disaster has been an earthquake and the least prevalent a hurricane. However, recent tracking of Disaster Medical Assistance Teams (DMATs) indicated that of late, the response to hurricanes is rising (FEMA, 2003;Mace, Jones, & Bern, 2007). While there is no U.S. region considered disaster-free, the South and the West reported the most events.…”
Section: Prevalencementioning
confidence: 99%
“…In the US, the DMATs also have been deployed for humanmade disasters including fires, 13 as well as terrorist attacks. 14 Japenese DMATs currently are expected to be deployed mainly for natural events such as earthquakes.…”
Section: Future Challengesmentioning
confidence: 99%
“…12 In the US, the DMATs are deployed to a variety of events, including many cases of slow-onset disasters such as floods. 13 In contrast, Japanese DMATs are small-scale and mobile. These small-scale teams are best suited for coping with the intense demands during the acute phase of disasters.…”
Section: Acknowledgementsmentioning
confidence: 99%